ANALISIS STRATEGI PEMASARAN UNTUK MENINGKATKAN DAYA TARIK PELANGGAN PADA UMKM SEMPRONG AMOUNDY KARAWANG - Asaibe Dorlima Simatupang; Sungkono (JOURNAL SAINS STUDENT RESEARCH, 2024)
Micro, Small and Medium Enterprises (UMKM) are independent small businesses run by community groups or families. As an important part of the economy, especially in Indonesia, UMKM have an important role in encouraging the growth of the community's economy in various sectors, including trade, agriculture, industry, services and other sectors. This research uses qualitative descriptive data with the methods used, namely library research, field research and interviews. . This information was obtained directly from the UMKM tofu factory by conducting observations and surveys based on interviews with respondents. Secondary data is information obtained in ready-to-use form such as library research, literature, the internet and various media. The results of the research show that marketing strategies that focus on the use of social media, targeted local promotions, and collaboration with local communities are very influential in increasing brand awareness. and attract new customers. These findings provide valuable insights for Semprong Amoundy Karawang UMKM and similar UMKM in developing relevant and effective marketing strategies to expand market share and increase competitiveness in the local market.